Effect of Budgetary Participation and Organizational Commitment on Budgetary Gaps - Cicilia Veronica Sigar; Tesalonika Mayawi Rau; Lilly Linne A Kainde (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of conducting this research is to find out also to prove whether the variables of budget participation and organizational commitment have an influence on the budgetary gaps that occur in the regional revenue and expenditure budget of Tomohon City. The independent variables in this study are budgetary participation and organizational commitment, while the dependent variable in this study is budget gaps. The research method used in this research is quantitative by using descriptive analysis. The samples for this study were 18 regional offices and agencies as well as companies that were part of the work unit of the regional apparatus of the City of Tomohon. Respondents to the questionnaire in this study amounted to 73 people consisting of heads of regional work units, secretaries of regional work units, heads of fields, and financial staff. The results obtained from the study state that budgetary participation has no effect on budget gaps. For organizational commitment, the results obtained state that this variable has a significant positive influence on the occurrence of budgetary gaps in the regional revenue and expenditure budget of Tomohon City. Participation and commitment of the budget preparers can reduce the occurrence of budgetary gaps, namely by being loyal and taking sides with the place where they serve